Energy budgeting of crop-livestock-poultry integrated farming system in irrigated ecologies of eastern India - KUMAR, SANJEEV; KUMAR, RAVI; DEY, AMITAVA (The Indian Journal of Agricultural Sciences, 2019)
The purpose of this study was to determine energy input, output and energy use efficiency of an acre land based crop-livestock-poultry IFS model, developed at ICAR-Research Complex for Eastern Region, Patna during 2012–16. In the current investigation, total energy input in the experimental one-acre integrated farming model was calculated to be 45.08 GJ and total energy output obtained as 102.54 GJ, and resulted in energy use efficiency ratio as 2.27. Also, it was analysed that total energy input was required utmost for the goat rearing, i.e. 24.84 GJ/20 goats/year followed by field crops, vegetable, green fodders, fruits, poultry and mushroom cultivation. In the current IFS model labour, diesel and electrical energy inputs were required maximum in field crops. The direct and indirect energy sources were calculated and found to be invested utmost in field crops and goat rearing as 2.98 GJ and 24.53 GJ, respectively. Similarly, renewable and non-renewable energy sources were utilized in goat rearing and field crops as 24.39 GJ and 6.99 GJ, respectively. Moreover, energy use efficiency ratio was estimated highest in fodder crops (8.66) and lowest from goat rearing (0.17). It was found that goatry and poultry farming are of least energy efficient agricultural production systems, because they produced negative energy mileage. The energy use efficiency ratio for the main output has shown that green fodders and field crops yielded better energy productivity. The net energy gain was recorded maximum from field crops. The energy profitability analysis revealed that green fodders’ cultivation was most profitable in terms of energy and produced EP ratio as 7.66 followed by field crops and vegetables, respectively.